Beneath The Shadow of “Java-Centrism”: Indonesian MSMEs Constraints during Pandemic - Nirwana, Aditya; Sukaton, Ounu Zakiy; Putri, Helga Carissa (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
Although Micro, Small, and Medium Enterprises (MSMEs) are often perceived as the most resilient sector during the COVID-19 pandemic, there has been no comprehensive study mapping the challenges faced by MSMEs in Indonesia throughout this period. The objective of this study is to provide a more complete overview of the constraints encountered by MSMEs during the COVID-19 pandemic in Indonesia and to compare the development of MSMEs during the pandemic with their geographical distribution across the country. Using a Systematic Literature Review (SLR) method and a narrative review approach, this study found that during the COVID-19 pandemic, Indonesian MSMEs primarily faced market-related constraints (39.47%), followed by knowledge constraints (34.21%), policy constraints (15.79%), and physical constraints (10.53%). A more detailed examination revealed that most MSMEs struggled with limited technological knowledge and skills (73%), followed by limited business knowledge (11%), difficulty in innovation (8%), lack of financial management knowledge (4%), and limited tax knowledge (4%). These challenges are interrelated, and many MSMEs experience multiple types of constraints simultaneously. The study also found that MSME development is predominantly concentrated on the island of Java compared to other islands, a phenomenon referred to as “Java-centrism.”